Cronkhite-Canada Syndrome Associated With Superficial Esophageal Carcinoma: A Case Report and Literature Review - Zhao, Yan; Lv, Fujing; Yang, Xun; Wang, Yongjun; Zhang, Shutian; Li, Peng (Frontiers in Medicine, 2022)
Introduction: Cronkhite-Canada syndrome is a rare disease characterized by generalized gastrointestinal polyposis, alopecia, skin pigmentation and onychotrophia with no generally recognized mechanism of pathogenesis. There is a tendency of malignant transformation or coexistence of gastrointestinal malignancies in patients with Cronkhite-Canada Syndrome. Endoscopic surveillance should be applied for early detection of any possible malignancies. Case description: The patient was a 67-year-old male who complained of dyspepsia, hair loss, skin hyperpigmentation and pedal edema. Lab tests showed hypoalbuminemia. Endoscopic findings included superficial esophageal carcinoma, numerous polyps in the stomach, duodenum and colon. The patient was treated with endoscopic submucosal dissection for the esophagus lesion, endoscopic mucosal resection for colon polyps and glucocorticoid for Cronkhite-Canada Syndrome. Conclusion: Esophagus cancer is a rare comorbidity of Cronkhite-Canada Syndrome. Endoscopic examination and surveillance are critical for patients with Cronkhite-Canada Syndrome for malignant gastrointestinal tumors.